EDUKASI PENGENALAN BENTUK SEDIAAN OBAT PADA SISWA KELAS 6 SDN PEKAPURAN RAYA 1: Introduction to the Forms of Medicinal Preparations Education for 6th Grade Students of SDN Pekapuran Raya 1 - Rusdahlia; Mardiati, Nurul; Abdina, Nisa (Program Studi Sastra Indonesia Universitas Mulawarman, 2025)
Abstract: This community service aims to introduce 6th-grade students of SDN Pekapuran Raya 1 to different drug dosage forms. The goal is to increase students' knowledge of various dosage forms such as tablets, capsules, liquid preparations, and others that are commonly used by children. The method used in this activity consists of educational discussions, pre-tests, and post-tests to assess students' understanding before and after the educational session. The results showed a significant improvement in students' knowledge, with the average post-test score reaching 100%, compared to an average pre-test score of 32%. This demonstrates the effectiveness of the educational intervention in enhancing the students' understanding of drug dosage forms. The findings suggest that similar education programs should be implemented to increase public awareness, especially among children, about the proper use of medications. Keywords: Drug preparations; education; community service; elementary school students Abstrak: Pengabdian masyarakat ini bertujuan untuk memperkenalkan siswa kelas 6 SDN Pekapuran Raya 1 pada berbagai bentuk sediaan obat. Tujuan kegiatan ini adalah untuk meningkatkan pengetahuan siswa tentang berbagai bentuk sediaan obat, seperti tablet, kapsul, sediaan cair, dan lainnya yang sering digunakan oleh anak-anak. Metode yang digunakan meliputi diskusi edukasi, pretest, dan posttest untuk menilai pemahaman siswa sebelum dan sesudah sesi edukasi. Hasil kegiatan menunjukkan peningkatan pengetahuan yang signifikan, dengan nilai rata-rata posttest mencapai 100%, dibandingkan dengan nilai rata-rata pretest sebesar 32%. Hal ini menunjukkan bahwa intervensi edukasi ini efektif dalam meningkatkan pemahaman siswa tentang bentuk sediaan obat. Temuan ini menyarankan agar program edukasi serupa dilakukan untuk meningkatkan kesadaran masyarakat, khususnya anak-anak, mengenai penggunaan obat yang tepat. Kata kunci: Sediaan obat; edukasi; pengabdian masyarakat; siswa sekolah dasar